N1-(2 tetrahydrofuryl)-5-fluorouracil (FT-207) in the postoperative adjuvant chemotherapy of gastric cancer. Delivery of a fat-emulsified agent to the lymph - Hanaue, H; Kurosawa, T; Kitano, Y; Miyakawa, S; Horie, F; Nemoto, A; Shikata, J (Cancer, 1986)
The influence of fat emulsification of N1-(2-tetrahydrofuryl)-5-fluorouracil (FT-207) on lymphatic transport was studied in seven postoperative gastric cancer patients. The water-in-oil-type of emulsion of FT-207 (FT-w/o), the oil-in-water-type emulsion of FT-207 (FT-o/w) and an enteric-coated granule of FT-207 (FT-G) each in 1-g doses, calculated in terms of FT-207, were administered orally. Lymph from a thoracic duct fistula, prepared in advance, and from the blood of a peripheral vein was collected simultaneously along a time course after administration to measure the concentrations of FT-207 and 5-fluorouracil (5-FU). For FT-w/o, FT-207, and 5-FU, concentrations were significantly higher, both in the lymph and in the blood, than those for FT-G and FT-o/w. However, no significant differences in FT-207 and 5-FU concentrations were observed between FT-o/w and FT-G. It was concluded that FT-w/o can be useful as an adjuvant chemotherapeutic drug in the postoperative treatment of gastric cancer.